CARS senses cysteine deprivation to activate AMPK for cell survival. (2nd September 2021) - Yuan, Mengqiu; Yan, Ronghui; Zhang, Yi; Qiu, Yue; Jiang, Zetan; Liu, Haiying; Wang, Ying; Sun, Linchong; Zhang, Huafeng; Gao, Ping
Abstract: Adenosine 5'‐monophosphate (AMP)‐activated protein kinase (AMPK) is an important cellular metabolite‐sensing enzyme that can directly sense changes not only in ATP but also in metabolites associated with carbohydrates and fatty acids. However, less is known about whether and how AMPK senses variations in cellular amino acids. Here, we show that cysteine deficiency significantly triggers calcium/calmodulin‐dependent protein kinase kinase 2 (CaMKK2)‐mediated activation of AMPK. In addition, we found that CaMKK2 directly associates with cysteinyl‐tRNA synthetase (CARS), which then binds to AMPKγ2 under cysteine deficiency to activate AMPK. Interestingly, we discovered that cysteine inhibits the binding of CARS to AMPKγ2, and thus, under cysteine deficiency conditions wherein the inhibitory effect of cysteine is abrogated, CARS mediates the binding of AMPK to CaMKK2, resulting in the phosphorylation and activation of AMPK by CaMKK2. Importantly, we demonstrate that blocking AMPK activation leads to cell death under cysteine‐deficient conditions. In summary, our study is the first to show that CARS senses the absence of cysteine and activates AMPK through the cysteine–CARS–CaMKK2–AMPKγ2 axis, a novel adaptation strategy for cell survival under nutrient deprivation conditions. Synopsis: Whether metabolite‐sensing enzyme AMPK regulates cell survival upon amino acid starvation, remains unclear. This study identifies the cysteine‐specific tRNA synthetase (CARS) as an activator of CaMKK2‐dependent AMPK signalling, revealing a novel cellular pathway for adapting to nutrient deprivation. Cysteine inhibits CaMKK2‐dependent activation of AMPK in human cancer cell lines. Cysteine depletion triggers binding of CARS to CaMKK2 and AMPKγ2, promoting AMPK phosphorylation at T172. The CARS‐CaMKK2‐AMPK axis promotes cell survival under cysteine‐deficient conditions. Abstract : AMP‐activated protein kinase AMPK senses low amino acid levels through a cysteine‐CARS‐CaMKK2‐AMPKγ2 axis.